Penggunaan Magnesium Sulfat pada Pasien dengan Asma Persisten Sedang Menjalani Operasi Elektif Tiroidektomi Total - Tyastarini, Ni Putu Ade Tiwi; Perdana , Aries (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2023)
Case: Female, 45 years old, with a history of moderate persistent asthma, type 2 diabetes mellitus, and bilateral struma multiple nodusa nontoxic (SMNT), planned to undergo a total thyroidectomy procedure. During the pre-anesthesia visit, it was found that the patient's condition was in acute exacerbation, then the night before the surgical procedure, the patient was given 2.5 mg salbutamol and Budesonide 5 mg inhalation. Magnesium sulfate (MgSO4) 25 mg/kg/kg intraveously in normal saline solution 100ml drip in 10 minutes, and continued with the administration of MgSO4 5 mg/kg/hour drip intravenously intra-operative. Post-operative, deep extubation was performed on the patient and monitored in the ICU for <24 hours, and continued in ward until allowed outpatient discharge on the second postoperative day. Discussion: In elective surgery particularly in the airway area, the risk of bronchospasm increases and optimal perioperative management is required as well as in patients with comorbid asthma. The administration of magnesium sulfate has several advantages in this case, in terms of the bronchodilation effect produced, as an adjuvant analgesia and also hypomagnesemia therapy related to diabetes mellitus. In conclusion, MgSO4 can be used as an alternative in the anesthetic modality of patients with a history of moderate persistent asthma who will undergo surgery.